Statistical and graphical (GGE biplot) evaluation of the adaptive ability and stability of winter barley breeding lines - V. N. Gudzenko (Вавиловский журнал генетики и селекции)
Due to current global climate changes, the issue of improving adaptive capacity of crops is of high importance. It is important to create winter crop varieties with both ecological adaptability and yield stability in years with different hydrothermal conditions. In order to develop winter barley varieties with a combination of yield and stability, 14 promising breeding lines have been evaluated in the conditions of the V.M. Remeslo Myronovka Institute of Wheat of NAAS of Ukraine in 2012/2013–2014/2015 using four different sowing dates. The ANOVA revealed a reliable part in yield variation: 64.59 % for environment, 16.84 % for genotype–environment interaction, and 15.57 % for genotype. The sowing dates significantly increased the yield variation of the breeding lines. The differences between the average yields of the lines depending on sowing date within the year were 1.05 t/ha in 2012/2013, 0.90 t/ha in 2013/2014, and 1.25 t/ha in 2014/2015. For genotype–environment interaction interpretation and ranking lines by yield a number of the most known statistical parameters of adaptability, stability, and plasticity and GGE biplot were applied. The use of different sowing dates at the final stage of the winter barley breeding process is a simple but effective approach that allows a more detailed assessment of the adaptive potential of breeding lines in various growing conditions. As compared to statistical parameters, GGE biplot has some advantages for interpretation of genotype–environment interaction. This graphic model allows ranking environments to be visualized for their discriminating ability and representativeness, as well as both specifically adapted genotypes and the ones with the optimal combination of yield potential and stability to be identified in a set of environments (mega-environment). The breeding line Pallidum 4816 with the optimal combination of yield and stability, as well as the high-yielding breeding lines Pallidum 4857 and Pallidum 4659 were identified and submitted to the State Variety Testing of Ukraine as the new winter barley varieties MIP Yason, MIP Oskar and MIP Hladiator.